2009
DOI: 10.1105/tpc.108.061812
|View full text |Cite
|
Sign up to set email alerts
|

ENDOSPERM DEFECTIVE1 Is a Novel Microtubule-Associated Protein Essential for Seed Development inArabidopsis 

Abstract: Early endosperm development involves a series of rapid nuclear divisions in the absence of cytokinesis; thus, many endosperm mutants reveal genes whose functions are essential for mitosis. This work finds that the endosperm of Arabidopsis thaliana endosperm-defective1 (ede1) mutants never cellularizes, contains a reduced number of enlarged polyploid nuclei, and features an aberrant microtubule cytoskeleton, where the specialized radial microtubule systems and cytokinetic phragmoplasts are absent. Early embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 66 publications
(74 reference statements)
1
102
0
Order By: Relevance
“…The spätzle mutant is characterized by the absence of cellularization in the endosperm but does not show cytokinesis defects in the embryo, indicating a role for SPÄTZLE in a process specific to endosperm cellularization (Sorensen et al, 2002). Similarly, in the endosperm defective 1 (ede1) mutant, the endosperm fails to cellularize but the effects on embryo patterning are less severe, implicating a main function for EDE1 in endosperm cellularization (Pignocchi et al, 2009). However, in both mutants, embryo development is delayed after the heart stage and seed shrinkage or collapse occurs, suggesting that endosperm cellularization is crucial for normal embryo and seed development (Sorensen et al, 2002;Pignocchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spätzle mutant is characterized by the absence of cellularization in the endosperm but does not show cytokinesis defects in the embryo, indicating a role for SPÄTZLE in a process specific to endosperm cellularization (Sorensen et al, 2002). Similarly, in the endosperm defective 1 (ede1) mutant, the endosperm fails to cellularize but the effects on embryo patterning are less severe, implicating a main function for EDE1 in endosperm cellularization (Pignocchi et al, 2009). However, in both mutants, embryo development is delayed after the heart stage and seed shrinkage or collapse occurs, suggesting that endosperm cellularization is crucial for normal embryo and seed development (Sorensen et al, 2002;Pignocchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the endosperm defective 1 (ede1) mutant, the endosperm fails to cellularize but the effects on embryo patterning are less severe, implicating a main function for EDE1 in endosperm cellularization (Pignocchi et al, 2009). However, in both mutants, embryo development is delayed after the heart stage and seed shrinkage or collapse occurs, suggesting that endosperm cellularization is crucial for normal embryo and seed development (Sorensen et al, 2002;Pignocchi et al, 2009). Interploidy crosses furthermore support an important role for endosperm cellularization in embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal effects play an important role in embryonic development in most animal species (for reviews, see Glover, 2005;Li et al, 2010;Lindeman and Pelegri, 2010) but have only recently been investigated in higher plants (for reviews, see Grossniklaus, 2005;Grossniklaus and Schneitz, 1998;Rodrigues et al, 2010). Like prl, about half of the gametophytic mutants in Arabidopsis display gametophytic maternal effects early in seed development (Moore et al, 2002;Pagnussat et al, 2005), including the well-studied FERTILIZATION-INDEPENDENT SEED (FIS) class genes (Chaudhury et al, 1997;Guitton et al, 2004;Köhler et al, 2003;Luo et al, 1999;Ohad et al, 1996;Ohad et al, 1999) and several cell cycle genes (Andreuzza et al, 2010;Pignocchi et al, 2009). How cell cycle regulators contribute to cellular differentiation is unclear because it is difficult to separate effects on proliferation and differentiation; but some, such as RBR, affect differentiation independently of their role in cell cycle regulation in both animals and plants (Inze and De Veylder, 2006;Johnston et al, 2010;Korenjak and Brehm, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Like ATK1, ATK4-like and ATK5, ATK4 clusters with the kinesin-14s, characterized by their C-terminal the specialized radial microtubule systems and cytokinetic phragmoplasts are absent. 15 This study also indicates that the MAPS, MAP65-1 and AtEB1c, may also play important roles that are specific to early endosperm development. Studies concerning these genes have revealed that MAP65s form 25 nm cross bridges between microtubules.…”
Section: Uncharacterized Genes With Strong Endosperm Expressionmentioning
confidence: 84%